Energy storage analysis of phase change materials (PCMs) integrated with thermal conductivity enhancers (TCEs). (9th December 2022) - Albojamal, Ahmed; Hamzah, Hudhaifa; Vafai, Kambiz
Abstract: A numerical analysis aiming to investigate the influence of numerous parameters on the energy storage systems has been conducted. The system performance working with phase change materials (PCMs) is evaluated in terms of complete melting time and metal foam radial distance in annulus. A comprehensive transient analysis is presented to monitor the melting behavior of the integrated PCM in the presence of porous metal foam sleeves under constant volume at various locations as thermal conductivity enhancers (TCEs). Aluminum alloy T-6201 is used for the porous metallic foam, while paraffin is introduced as PCM. The porosity, pore size (PPI), various PCM materials, and porous distance from the heat sources were investigated. Results show that porous TCEs radial distance from the applied heat sources has a substantial effect and can lead to an improved rate of melting depending on the sleeve location. In addition, high thermal conductivity near the heat source suppresses the porous resistance to liquid PCM flow and thus natural convection. Results revealed that case B provides a uniform liquid PCM profile and heat distribution while case D has the highest melting during the initial stage and lower one at the final stages of melting. Pure PCM case imposed the least resistance but has the slowest melting time while a turning point in melting rate is noticed from case C. Eventually, results show that higher PPI materials have a similar melting pattern as a result of high thermal conductivity.